2019
DOI: 10.1016/j.tourman.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Hospitality servicescape effects on customer-employee interactions: A multilevel study

Abstract: Servicescapes are the manmade environments where hospitality activities, such as dining and lodging, occur. For more than two decades tourism and hospitality research has sought to understand the impact of hospitality servicescapes, primarily on hospitality customers and, to a lesser degree, on hospitality customer-contact employees. So far no empirical study has investigated, however, how servicescapes affect the interactions of customers with employees; there is therefore no empirical evidence that hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 159 publications
(173 reference statements)
6
39
0
5
Order By: Relevance
“…Tangibles were found to be the third most important quality attribute. This finding is also in agreement with the results of previous studies (Kaminakis et al, 2019;Wu & Mohi, 2015), which showed that guests' satisfaction in restaurants is also highly influenced by the quality of the physical environment. According to Raajpoot (2002), tangible quality (the physical environment) provides the necessary prerequisite for delivering functional quality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tangibles were found to be the third most important quality attribute. This finding is also in agreement with the results of previous studies (Kaminakis et al, 2019;Wu & Mohi, 2015), which showed that guests' satisfaction in restaurants is also highly influenced by the quality of the physical environment. According to Raajpoot (2002), tangible quality (the physical environment) provides the necessary prerequisite for delivering functional quality.…”
Section: Discussionsupporting
confidence: 93%
“…The scientific literature has clearly highlighted the importance of quality for the restaurant industry. Therefore, restaurant management should be marketoriented and should clearly understand the needs and expectations of current and future guests (Kaminakis et al, 2019). Although management's unrealistic perceptions of guests' quality expectations represent the first gap in providing high-quality services (Parasuraman et al, 1988), only a few studies (Kukanja & Planinc, 2018;Namkung & Jang, 2008) have investigated the importance of different quality attributes for providing highquality service to guests, according to restaurant managers' beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the service process could be standardized, the need for human resources cannot be reduced. In particular, frontline employees play the role of service delivery [1] and maintain the customer relationship and image building for the organization [2]. Frontline employees, therefore, are the key to establishing contact between businesses and customers, as well as the primary connection.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the authors suggests that the management of Ticket's Café should conduct more elaborate training not only on how to upsell, but also how to upsell more so the number of employees will not be an issue. K. Kaminakis et al (2018) claim that servicescapes works effectively as a tool for managers to achieve their goals. It can be implemented with rewards, coaching, training, collaboration, and innovativeness.…”
Section: Resultsmentioning
confidence: 99%